Relação entre desempenho escolar em ciências e possíveis indicadores de distúrbios de aprendizagem - Faria, Taciana de Lisboa (2015)
Research indicates that environmental and biological factors are directly related to the child's school performance. Therefore, this study aimed to tailor a performance test of Science to Brazilian students with possible learning disorders indicators. Research characterized as qualitative and quantitative developed in two stages. The first was the construction and implementation of a large-scale performance testing of a sample 334 students in states of four regions of the country: Mato Grosso, Rio Grande do Sul, Sao Paulo and Sergipe. The application was done in schools that had computers with internet, since 229 students completed the test in the online version and 105 in the print version. The second phase of the research involved the adaptation and application of a questionnaire measuring biological and environmental indicators related to neural organization of the child applied to 128 mothers / guardians of students in the first three states mentioned. The questionnaire, adapted from the Rocha and Rocha Research (2009) was composed of objective and Likert questions which were structured in four main dimensions: pregnancy, childbirth, early childhood and family history. For the analysis, the data were divided into 3 categories, namely: physiological factors, psychological factors and hereditary factors. For the test analysis, the questions were divided into four groups: issues up to 40% accuracy, 40 to 50% accuracy, and 50-70% accuracy and over 70% accuracy. The data obtained from the application of the instruments were tabulated and processed in statistical software and show the relative frequencies of the indicators and the performance of the sampled students. There was no significance to fold our performance data with indicators, which makes us realize that the suitability of a teaching methodology means that there is no identification of differences in student performance, is taken into account students' singularities. This makes us reflect that, in case of performance tests, changes in the educational process allows adjustments to the uniqueness of the students, breaking the paradigm that the doctor diagnosed as incapable.